In Vivo Bone Effects of a Novel Bisphosphonate‐EP4a Conjugate Drug (C3) for Reversing Osteoporotic Bone Loss in an Ovariectomized Rat Model. (9th November 2019) - Sheikh, Zeeshan; Chen, Gang; Al‐Jaf, Faik; Thévenin, Marion; Banks, Kate; Glogauer, Michael; Young, Robert N; Grynpas, Marc D
ABSTRACT: Pathological bone loss is a regular feature of postmenopausal osteoporosis, and the microstructural changes along with the bone loss make the individual prone to getting hip, spine, and wrist fractures. We have developed a new conjugate drug named C3, which has a synthetic, stable EP4 agonist (EP4a) covalently linked to an inactive alendronate (ALN) that binds to bone and allows physiological remodeling. After losing bone for 12 weeks, seven groups of rats were treated for 8 weeks via tail‐vein injection. The groups were: C3 conjugate at low and high doses, vehicle‐treated ovariectomy (OVX) and sham, C1 (a similar conjugate, but with active ALN at high dose), inactive ALN alone, and a mixture of unconjugated ALN and EP4a to evaluate the conjugation effects. Bone turnover was determined by dynamic and static histomorphometry; μCT was employed to determine bone microarchitecture; and bone mechanical properties were evaluated via biomechanical testing. Treatment with C3 significantly increased trabecular bone volume and vertebral BMD versus OVX controls. There was also significant improvement in the vertebral load‐bearing abilities and stimulation of bone formation in femurs after C3 treatment. This preclinical research revealed that C3 resulted in significant anabolic effects on trabecular bone, and EP4a and ALN conjugation components are vital to conjugate anabolic efficacy. A combined therapy using an EP4 selective agonist anabolic agent linked to an inactive ALN is presented here that produces significant anabolic effects, allows bone remodeling, and has the potential for treating postmenopausal osteoporosis or other diseases where bone strengthening would be beneficial. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.